THE USE OF REFLEXIVE METADISCOURSEBETWEEN ENGLISH AND INDONESIAN WRITERS IN ENGLISH JOURNAL ARTICLES - Candra Ayu Putri Darma (Language-Edu, 2021)
ABSTRACTFor second language writers to write English research articles (RAs), it seems really challenging for them to write academic articles by English. In order to make the good and understandable writing the use of metadiscourse is really important. Therefore, this study attempted to explore the comparison of using metadiscourse for two different authors, the English native and Indonesian authors in their RAs. This study focused on the introduction and discussion section only. It aimed to identify the differences between the authors and to investigate how they used metadiscourse in their texts.The subject of this study comprised in total, 10 introductions and 10 discussions from 10 journals which are 5 different articles for each English native journals and Indonesian journals. They are in the field of TESOL and applied linguistic. This study focused on Ädel (2006) reflexive metadiscourse model (i.e., personal and impersonal metadiscourse) as the analytical framework. This study found that the culture influenced the use between personal and impersonal metadiscourse. The English native authors used more personal metadiscousre. On the other side, the Indonesian authors seems comfortable to use impersonal one.Keywords: “impersonal metadiscourse”, “personal metadiscourse”, “reflexive approach of metadiscourse”